On culture, ethics, and hierarchy: How cultural variations in hierarchical relations are manifested in the code of ethics of British and Korean organizations. Issue 1 (7th November 2017) - Moon, Chanki; Uskul, Ayse K.; Weick, Mario
Abstract: The present research examined if cultural differences in the extent to which hierarchical relations dictate individuals' behaviors are embedded in objective institutional regulations. Using quantitative and qualitative analysis, we examined codes of ethics of Korean and British organizations in relation to working relationships and corruptive behaviors. We found that, unlike British organizations, Korean organizations endorsed codes of ethics that place greater emphasis on hierarchical relations and contained prescriptions for individuals occupying senior or junior ranks. Ethical codes also appeared to be geared more towards preventing the abuse of power in Korean organizations compared with British organizations. Finally, unlike British organizations, Korean organizations often permitted top‐down exchanges (not bottom‐up exchanges), suggesting that in upper echelons benevolence may be more normative in Korean organizations than in British organizations.